Acidity of Isomorphic Substituted Zeolites with B, Al and Ga Revisited - Petelski, Andre Nicolai (2024)
Isomorphic substitution of zeolites with B, Al and Ga is a widely used approach in catalysis. The experimentally reported trend of their acidities decreases in the order: Al > Ga > B. However, a consistent explanation is still lacking in the literature. To bring more understanding of this trend, density functional theory computations were conducted on several model systems. First, the acidity of small clusters with two (2T) and five (5T) tetrahedral sites was analyzed. These systems were then projected onto three large void structures: H-[A]-BEA (52T), H-[A]-FAU (84T) and H-[A]-MOR (112T) with A = B, Al, Ga. Our electron density and Interacting Quantum Atom analyses show that the acidity of Al zeolites originates from the much stronger O–Al bond, which is dominated by the electrostatic attraction. The bridging hydroxyl therefore donates more charge density to the metal, the proton becomes more positive and consequently more acidic. Ga zeolites are more acidic than B zeolites due to the greater covalent nature on the O–Ga bond. The resulting acidity, as seen by ammonia, depends on both the acidic oxygen and the charge distribution of the surrounding oxygens exerted by the substituents.